2012
DOI: 10.1186/2191-219x-2-22
|View full text |Cite
|
Sign up to set email alerts
|

FDG-PET is a good biomarker of both early response and acquired resistance in BRAFV600 mutant melanomas treated with vemurafenib and the MEK inhibitor GDC-0973

Abstract: BackgroundThe BRAF inhibitor, vemurafenib, has recently been approved for the treatment of metastatic melanoma in patients harboring BRAFV600 mutations. Currently, dual BRAF and MEK inhibition are ongoing in clinical trials with the goal of overcoming the acquired resistance that has unfortunately developed in some vemurafenib patients. FDG-PET measures of metabolic activity are increasingly employed as a pharmacodynamic biomarker for guiding single-agent or combination therapies by gauging initial drug respon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
59
0
3

Year Published

2013
2013
2017
2017

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 55 publications
(73 citation statements)
references
References 40 publications
6
59
0
3
Order By: Relevance
“…This possibility has not been directly tested yet, but vemurafenib treatment of drug 20 resistant A375 melanoma cells (which express B-RafV600E) elevated the concentrations of KSR1 and Raf-1 proteins, and enhanced ERK activation. 63 Unfortunately, the dimerization status of KSR1, B-Raf and Raf-1 was not determined in this study, but based on the KSR studies described above 25, 62 25 expression changes should influence which dimers are formed, suggesting that KSR may play a role in the resistance to Raf inhibitors.…”
Section: Raf Dimerization and Drug Resistancementioning
confidence: 87%
“…This possibility has not been directly tested yet, but vemurafenib treatment of drug 20 resistant A375 melanoma cells (which express B-RafV600E) elevated the concentrations of KSR1 and Raf-1 proteins, and enhanced ERK activation. 63 Unfortunately, the dimerization status of KSR1, B-Raf and Raf-1 was not determined in this study, but based on the KSR studies described above 25, 62 25 expression changes should influence which dimers are formed, suggesting that KSR may play a role in the resistance to Raf inhibitors.…”
Section: Raf Dimerization and Drug Resistancementioning
confidence: 87%
“…Cobimetinib in combination with vemurafenib was associated with a greater inhibition of signaling, increased tumor cell apoptosis and better tumor response than vemurafenib alone in preclinical cancer models [5,12]. Moreover, tumor samples from patients with BRAF V600 mutation-positive locally advanced or metastatic melanoma participating in the BRIM7 study and receiving combination treatment with cobimetinib and vemurafenib showed robust modulation of tumor cell signaling and transcription [13].…”
Section: Breast Cancermentioning
confidence: 98%
“…A inibição direta e específica da quinase mutada mostrou uma redução significativa no crescimento do tumor e aumento na sobrevida do paciente (Blue Cross and Blue Shield Association, 2015). O vemurafenibe (GDC-0941) é um inibidor competitivo do domínio quinase do oncogene BRAF, disponível para administração oral (Baudy et al, 2012). Esse medicamento suprime o fluxo de sinalização por meio da inibição da quinase serina-treonina BRAF, inibindo a proliferação celular em células tumorais que possuem gene BRAF com mutações V600 (Produtos Roche Químicos e Farmacêuticos S.A., 2014).…”
Section: Introductionunclassified
“…Esse medicamento suprime o fluxo de sinalização por meio da inibição da quinase serina-treonina BRAF, inibindo a proliferação celular em células tumorais que possuem gene BRAF com mutações V600 (Produtos Roche Químicos e Farmacêuticos S.A., 2014). Além disso, o vemurafenibe demonstrou resultados positivos em pacientes portadores da mutação BRAF V600E , resultando em regressão quase total do tumor e sobrevida livre de progressão (SLP) de sete meses (Baudy et al, 2012).…”
Section: Introductionunclassified
See 1 more Smart Citation